Gender understanding and awareness among employees in selected government agencies: a qualitative analysis - Wan Jaafar, Wan Munira; Ahmad, Nobaya; Md Noor, Amna (Universiti Putra Malaysia Press, 2019)
This study focuses on understanding the level and awareness of gender equality concepts among civil servants in selected agencies under The Ministry of Women, Family and Community Development, Malaysia (MWFCD). The paper is based on the findings made on a part of the study on knowledge of gender issues which was obtained through Focus Group Discussion (FGD) analysis. A total of 38 informants consisting of 15 officers from professional groups and 23 support groups of six government agencies were involved in the data collection process. The group division aimed to look at the differences in their views based on gender dissimilarity. The study found that most informants demonstrated moderate understanding on the meaning of gender but were able to distinguish between the concepts of 'gender' and 'sex' in terms of biological definition and social roles. Understanding level among the informants differs due to certain characteristics such as social background, service grade and the assigned department. In general, informants gave a high credential to the role and equal rights in between the sexes and showed great awareness on gender issues that arose. However, dissatisfaction related to men welfare issue was indicated by the male informants as they perceived that they were not enjoying the same privileges as women. Overall, the women's group informants among both professional and support staff showed a fair awareness of gender equality as compared to the men. In conclusion, informants in the study have demonstrated a good level of understanding and awareness on gender equality issues. However, some improvements in terms of training and practices are needed to ensure substantial execution of gender mainstreaming among all civil servants in Malaysia as recommended by "Corong Model" introduced by the research at the end of the study.